Implicit motives and children's salivary cortisol reactivity to an adapted version of the Trier Social Stress Test for Children (TSST-C). (1st August 2020) - Spengler, Benedikt; Hofer, Jan; Busch, Holger; Dzionsko, Inga; Emslander, Valentin
Abstract: This research addresses the interplay between two implicit motives, that are power (nPow) and affiliation (nAff), and the cortisol reactivity (CR) to a psychosocial stressor (an adaption of the Trier Social Stress Test for Children; TSST-C; Buske-Kirschbaum et al., 1997) in 89 healthy children (45 female; M age  = 7.74, SD Age  = 0.46). We assessed implicit motives by a 6-image Picture Story Exercise (PSE) and cortisol by 6 saliva samples. As hypothesized, the procedure triggered a significant cortisol reaction, F (1.44, 127.05Greenhouse-Geisser ) = 8.22, p  = .002, η 2 part  = 0.09. Contrary to our hypothesis, children high in nPow showed no significant increase in CR ( β  = 0.06, p  = .60). However, our results were in line with the findings of Wegner, Schüler, and Budde (2014) that a high implicit affiliation motive is associated with an attenuated CR ( β  = −0.21, p  = .05). Perspectives for future research on implicit motives and children's CR to psychosocial stress are discussed. Highlights: An adapted version of the Trier Social Stress Test for Children is introduced. The adapted Trier Social Stress Test for Children triggered a cortisol reaction. Children's implicit power motive did not correlate with their cortisol reaction. Implicit affiliation was positively associated with an attenuated cortisol reaction.